Multi-skilling in small- and medium-sized engineering firms : evidence from Wales and Germany - Scott, Peter [Verfasser]; Cockrill, Antje [Verfasser] (My University, 1997)
" A cross-national empirical study of forty-six engineering SMEs in Wales and two regions of Germany analyses the extent to which multi- skilling of staff is occuring, the underlying reasons for such developments, and how well placed firms are in relation to prevailing labour-market and training infrastructures strategically to develop hybrid occupations. We identify four types of skill accredition, only some of wich presage net enhancements of the order of skills exercized. New quality assurance or continuous improvement programmes, and organizational restructuring, were the main reasons for multi-skilling. A majority of companies encouraged skill expansion on an ad hoc basis, yet strategic exploitation of multi- skilling incorporating comprehensive training support remained infrequent, especially in Germany. Nevertheless, a minority of the German multi-skilling leads to the award of innovative "hybrid" qualifications fusing two skilled occupations. The breadth of German initial craft training both facilitates and inhibits potential for further multi skilling in practice. In Wales, greater flexibility in occupational and training structures provides largely unrealized potential advantages over Germany in developing multi-skilling, especially as a means to resolve recurrent shortages of skilled workers. Welsh SMEs have preferred tentative, incremental, "bolt-on" approaches to multi-skilling that facilitate only limited external transferability. (author-s abstract, IAB-Doku) ((en)) Die empirische Studie untersucht vergleichend zwischen der Bundesrepublik und Wales das Ausmass und die Ursachen von Mehrfachqualifizierung in Klein- und Mittelbetrieben des Maschinenbaus. (IAB)
Keywords: S 3.2.1 KMU, Klein- und Mittlere Unternehmen; S 1.3.4 Doppelqualifizierende Bildungsgänge; S 6.2.3 Metallerzeugung und -bearbeitung, Maschinenbau, Montierberufe (inkl. fahrzeugtechnischer Berufe); I 2.2.1 Westeuropa; Kleinbetrieb; Mittelbetrieb; Doppelqualifikation; Internationaler Vergleich; Berufliche Qualifikation; Berufliche Weiterbildung; Maschinenbau; Personalpolitik; Personalentwicklung; Großbritannien; 1996-1996